Urinary S-PMA related to indoor benzene and asthma in children. (June 2013) - Rive, S.; Hulin, M.; Baiz, N.; Hassani, Y.; Kigninlman, H.; Toloba, Y.; Caillaud, D.; Annesi-Maesano, I.
Abstract Introduction: Benzene is a ubiquitous pollutant of both indoor and outdoor environments which impacts on respiratory health. Our aim was to relate urinary S-phenylmercapturic acid (S-PMA), a biomarker of benzene exposure, to benzene concentrations and related sources at home and asthma in a population-based sample of children. Methods: Exposure to benzene was assessed in the dwellings of 63 children (32 asthmatics and 31 controls) through the identification of sources of benzene and in situ assessments with passive samplers. The determination of urinary S-PMA was obtained by liquid chromatography–mass spectrometry. Results: At home, asthmatics were significantly more polluted by benzene levels from ambient sampling than controls (p ≤ 0.05). Benzene exposure significantly aggravated asthma symptoms overall in non-atopic children (OR = 10.10; 95% confidence interval: 10.10). Urinary S-PMA was significantly associated with benzene concentrations in the entire population (regression coefficient = 0.28, 95% CI: 0.07–0.49; p < 0.05) and asthma (OR = 7.69; 95% CI: 1.37–42.52 for an increase of 1 µg/g creatinine of urinary S-PMA). However, after adjustment for environmental tobacco smoking exposure, familial allergy, age and sex, the latter relationship was no more significant (OR = 4.95; 95% CI: 0.91–27.4, p < 0.10). Both benzene concentrations and urinary S-PMA concentrations were higher in dwelling built after 1948 and in flats. Conclusions: Our study suggests a relationship between childhood asthma and benzene concentrations at home, even at low levels of this pollutant. This was confirmed when considering urinary S-PMA, which was related to both benzene concentrations and asthma. Further epidemiological and toxicological studies are needed to confirm our results.